2010
DOI: 10.1111/j.1365-2214.2009.01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Parenting stress in US families: implications for paediatric healthcare utilization

Abstract: Having a parent who is experiencing high parenting stress is associated with greater utilization of paediatric emergency care. Interventions targeted at parenting stress may provide families with needed support and reduce unnecessary emergency care utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 40 publications
4
82
0
1
Order By: Relevance
“…Low emotional and practical support have previously been shown to be associated with health care seeking [28,29]. For example, a recent American study showed that children whose parents experienced low emotional support had higher odds for having paid visits to primary care with the child [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low emotional and practical support have previously been shown to be associated with health care seeking [28,29]. For example, a recent American study showed that children whose parents experienced low emotional support had higher odds for having paid visits to primary care with the child [28].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent American study showed that children whose parents experienced low emotional support had higher odds for having paid visits to primary care with the child [28]. Poor maternal psychosocial functioning may influence the child's psychosocial and physical health both directly, by inhibiting the mother's ability to care for the child, and also indirectly through her limited personal resources to help her child by turning to a physician for assistance [29].…”
Section: Discussionmentioning
confidence: 99%
“…Mothers go through a complex decision-making process when their children are unwell, which is influenced by the mother's psychological state 1. Mothers from a military family are often alone and emotionally vulnerable when their partner is absent on deployment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, secondary data analysis of HCUD can yield significant findings that can positively or negatively affect the direction of future studies. For instance, a utilization study by Raphael, Zang, Liu & Giardino (2010) used national children’s health data to investigate the relationship between high parenting stress and healthcare utilization, finding a significant correlation between increases in parenting stress and the frequency of emergency care visits. Even controlling for psychosocial and sociodemographic variables, they determined that parents with high parenting stress were more likely (adjusted odds ratio, 1.24; 95% confidence interval 1.10–1.41) to seek emergency care for their children compared to parents with low parenting stress.…”
Section: Healthcare Utilization and Its Contribution To Clinical Outcmentioning
confidence: 99%